COMPOUNDING WORDS ; WORDS FORMATION IN REPUBLIKA NEWSPAPERS - Eripuddin; Liana Fuji Lestari (JEE (Journal of English Education), 2019)
This study investigated words formation that found in the republika newspaper. The research was a descriptive qualitative research design . The object of this research was headline of Republika Newspaper. The instrumentation of the reserach was documentation. The data were consisted of 96 data The data were analyzed by using the theory of word formation (O’ Grady, 1996) The results of this research shown that 70 datawere classified as endocentric compound and transparent meaning and 26 data were categorized in exocentric compound and opaque meaning. Transparent meant that the meanings of the words could be predicted from the each of the word. Opaque meant that the meaning of words could not predicted from the each of word.